A multiaxial inertial macroelement for bridge abutments. (27th January 2023) - Gorini, Davide Noè; Callisto, Luigi; Whittle, Andrew J.; Sessa, Salvatore
Abstract: This paper proposes a multiaxial macroelement for bridge abutments that can be included in the global structural model of a bridge to carry out nonlinear dynamic analyses with very much smaller computational effort than can be achieved using continuum representations of embankment and foundation soil behaviour. The proposed macroelement derives a constitutive force–displacement relationship within a rigorous thermodynamic framework and includes important features of non‐linearity and directional coupling in characterizing the interactions of the abutment with the soil. In a dynamic analysis, the frequency‐dependent response of the system is simulated through the combination of the macroelement with appropriate participating masses. The calibration procedure of the macroelement is based on the assessment of its ultimate capacity and of its response at small displacements, and it is shown that these ingredients can be derived through standardised procedures. In the paper, the macroelement response is validated against the results of fully coupled continuum numerical analyses for a reference soil–abutment system, under both static and seismic loading conditions. We show that the two models achieve similar predictions of maximum and permanent abutment deformations (less than 10–14% difference, respectively) for a suite of three‐axis seismic loading events.